ANTIOXIDANT AND ANTI-INFLAMMATORY ACTIVITIES OF STEVIA REBAUDIANA LEAF EXTRACT IN DIABETIC RATS - Eidangbe, George O. (FUDMA JOURNAL OF SCIENCES, 2025)
This study explores the antioxidant and anti-inflammatory effects of Stevia rebaudiana aqueous leaf extract in alloxan-induced diabetic male Wistar rats. Thirty rats, comprising six normoglycemic controls (NC) and twenty-four diabetic rats were used. The diabetic rats were divided into four groups (n = 6 each): DC, diabetic rats administered distilled water; DGL, diabetic rats treated with glibenclamide; DSR100 and DSR200, diabetic rats treated with 100 and 200 mg/kg S. rebaudiana extract, respectively. Treatments were administered daily via gavage for 15 days. After 15 days, animals were fasted overnight, euthanized by cervical dislocation, and blood samples collected for serum analyses. Body weight, liver weight, fasting blood glucose (FBG), and serum malondialdehyde (MDA) level were monitored. Antioxidant enzyme activitiessuperoxide dismutase (SOD), catalase (CAT), and glutathione peroxidase (GPx)were also measured, alongside serum levels of pro-inflammatory cytokines interleukin-1 (IL-1), tumor necrosis factor- (TNF-), and the anti-inflammatory cytokine interleukin-10 (IL-10). The findings revealed that S. rebaudiana extract significantly reduced serum MDA levels and enhanced the activities of antioxidant enzymes (SOD, CAT, and GPx) in diabetic rats. Significant (p<0.05) improvements in FBG, liver-to-body weight ratio, and cytokine profiles were observed in the DSR100 and DSR200 groups compared with the DC. Specifically, the extract significantly decreased IL-1 and TNF- while elevating IL-10 level. These effects were dose-dependent, with 200 mg/kg dose showing the most pronounced benefits. In conclusion, aqueous leaf extract of S. rebaudiana demonstrates robust antioxidant and anti-inflammatory activities, effectively attenuating oxidative stress-induced inflammatory responses in alloxan-induced diabetic rats.